Unifying dose specification between clinical BNCT centers in the Americas - Riley, K. J. (2008)
A dosimetry intercomparison between the boron neutron capture therapy groups of the Massachusetts Institute of Technology MIT and the Comisión Nacional de Energía Atómica CNEA, Argentina was performed to enable combined analyses of NCT patient data between the different centers. In-air and dose versus depth measurements in a rectangular water phantom were performed at the hyperthermal neutron beam facility of the RA-6 reactor, Bariloche. Calculated dose profiles from the CNEA treatment planning system NCTPlan that were calibrated against in-house measurements required normalizations of 1.0 thermal neutrons, 1.13 photons, and 0.74 fast neutrons to match the dosimetry of MIT.